Splicing factor SF3B1(K700E) mutant dysregulates erythroid differentiation via aberrant alternative splicing of transcription factor TAL1 - Jin, Shuiling (PLoS One, 2017)
More than 60% of myeloid dysplasia syndrome (MDS) contains mutations in genes encoding for splicing factors such as SF3B1, U2AF, SRSF2 and ZRSR2. Mutations in SF3B1 are associated with 80% cases of refractory anemia with ring sideroblast (RARS), a subtype of MDS. SF3B1(K700E) is the most frequently mutated site among mutations on SF3B1. Yet the molecular mechanisms on how mutations of splicing factors lead to defective erythropoiesis are not clear. SF3B1(K700E) mutant binds to an RNA binding protein, RBM15, stronger than the wild type SF3B1 protein in co-immunoprecipitation assays. In addition, K700E mutant alters the RNA splicing of transcription factors TAL1 and GATA1. Via alternative RNA splicing, a novel short TAL1 transcript variant (TAL1s) is generated. Enhanced interaction between SF3B1 and RBM15 promotes the production of full-length TAL1 (TAL1fl) mRNA, while reduction of RBM15 protein level via PRMT1-mediated degradation pathway changes TAL1s/TAL1fl ratio in favor of TAL1s. TAL1s contains the helix-loop-helix DNA binding domain but not the N terminal region upstream of the DNA binding domain. The TAL1s protein loses its interaction with ETO2, which represses early erythropoiesis. In this vein, overexpression of TAL1s stimulates the transcription of β-hemoglobin in human leukemia K562 cells and promotes erythroid differentiation of human cord blood CD34(+) cells cultured in erythropoietin-containing medium. Therefore, mutations of SF3B1 may block erythropoiesis via dysregulation of alternative RNA splicing of transcription factor TAL1, and targeting PRMT1 may alleviate the anemic symptoms in MDS patients.